Technical Trick: T-Bar External Fixator for Definitive Management of Periarticular and Metadiaphyseal Tibial Fractures. Issue 1 (3rd March 2023) - Mease, Samuel J.; Bradley, Hallie R.; Thota, Dharani R.; Starr, Adam J.; Sanders, Drew T.
Abstract : Purpose: Tibia fractures with soft tissue compromise present are challenging to manage. For fractures with significant swelling or open injury not amenable to internal stabilization, external fixators provide sufficient stability for bony healing. Ring fixators and hybrid constructs provide adequate stability for healing but are costly, and challenging to apply and maintain. We present the "T-bar" external fixator, a novel construct that can be maintained until bony union and allows for range of motion of adjacent joints. We also report the demographics, clinical, and radiographic outcomes of 34 patients treated definitively with this construct. Materials and Methods: The T-bar external fixator uses standard pins and bars in a novel arrangement. It can be applied for Arbeitsgemeinshaft fur Osteosynthesefragen/Orthopaedic Trauma Association-type 41/42/43 type injuries, with or without supplemental fixation for intra-articular patterns. Results: Between 2008 and 2015, 34 patients were treated for tibia fracture with T-bar external fixation, with intention to treat in a definitive manner. Twenty-nine were male, and average age was 44.3 years. Thirty-one sustained high energy mechanisms of injury. Twenty were Gustilo-type 2 or 3 fractures. Of 14 closed fractures, 12 were Tscherne-type 2 or 3. Conclusions: The T-bar external fixator offers an alternative to ring and hybrid external fixator constructs in treatment of tibia fractures with significant soft tissue compromise. Of 28 patients with complete follow up, only 1 case of osteomyelitis was reported. All patients were managed without amputation. Three required revision for nonunion, all Arbeitsgemeinshaft fur Osteosynthesefragen/Orthopaedic Trauma Association-type 43.